1994
DOI: 10.1161/01.hyp.24.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension induced by a nonpressor dose of angiotensin II in kininogen-deficient rats.

Abstract: Brown Norway Katholiek rats with very low levels of plasma kininogens excreted a much smaller amount of kinin in the urine than normal rats of the same strain. The systolic blood pressure of 7-week-old kininogen-deficient rats (132±2 mm Hg, n=7) was not different from that of normal rats. Angiotensin II (Ang II) (20 jig/d SC) from 7 weeks of age for 2 weeks with a micro-osmotic pump caused significant increases in blood pressure (181 ±5 mm Hg, n=7, 9 weeks old) in the deficient rats, although the same treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 37 publications
(36 reference statements)
2
65
0
Order By: Relevance
“…12 In this regard, Majima et al 13 found that DOCA-salt induced a faster rise in systolic pressure in kinin-deficient rats (Brown Norway Katholiek, BNK) than controls; moreover, BNK given a high-salt diet or chronic infusion of Ang II become hypertensive compared with controls. 14,15 On the other hand, using a different approach, Madeddu et al 16,17 reported that chronic blockade of B 2 receptors with icatibant made rats hypertensive when given a high-salt diet or chronically infused with Ang II. Both Majima and Madeddu concluded that kinins prevent the chronic hypertensinogenic effect of DOCA-salt, high salt or Ang II.…”
mentioning
confidence: 99%
“…12 In this regard, Majima et al 13 found that DOCA-salt induced a faster rise in systolic pressure in kinin-deficient rats (Brown Norway Katholiek, BNK) than controls; moreover, BNK given a high-salt diet or chronic infusion of Ang II become hypertensive compared with controls. 14,15 On the other hand, using a different approach, Madeddu et al 16,17 reported that chronic blockade of B 2 receptors with icatibant made rats hypertensive when given a high-salt diet or chronically infused with Ang II. Both Majima and Madeddu concluded that kinins prevent the chronic hypertensinogenic effect of DOCA-salt, high salt or Ang II.…”
mentioning
confidence: 99%
“…Moreover, wild-type mice or mice with the TK gene deleted exhibited a similar increase in blood pressure when renovascular hypertension was induced (129), further supporting the concept that the KKS plays no more than a minor role in blood pressure regulation either under normal conditions or during hypertension. In kininogen-deficient Brown Norway Katholiek rats (BNK), administration of mineralocorticoids and salt or angiotensin II reportedly increased blood pressure to the same degree as rats with a normal KKS (229), contradicting reports by other investigators (150)(151)(152). Thus, taken together the published data would suggest that kinins are not critical for blood pressure regulation, nor are they required for the development of hypertension, save perhaps in salt-sensitive animals.…”
Section: Kinins In Blood Pressure Regulation and The Pathogenesis Of mentioning
confidence: 95%
“…Chronic blockade of B 2 receptors with a potent and selective antagonist, icatibant, did not increase blood pressure under normal conditions or in situations that favor hypertension in rats, such as (i) chronic infusion of a subpressor or pressor dose of angiotensin II (Ang II), (ii) a high salt diet, or (iii) mineralocorticoids and salt (148,229). However, other researchers have had entirely different results, who found that lack circulating kininogen or blockade of B 2 receptors are associated with significant increases in blood pressure under normal conditions or when animals are challenged with a pressor agent or diet (147,(150)(151)(152).…”
Section: Kinins In Blood Pressure Regulation and The Pathogenesis Of mentioning
confidence: 99%
“…Tissue kallikrein cleaves lowmolecular-weight kininogen substrate to produce the vasodilator Lys-bradykinin, whereas plasma kallikrein forms bradykinin (BK) from high-molecular-weight kininogen (HMWK). Kininogen-deficient rats are susceptible to the development of salt-induced hypertension (28), and the in vivo angiogenesis is suppressed (29). The proangiogenic effect of BK and HMWK has been demonstrated in both in vitro and in vivo studies (30).…”
Section: Antiphospholipid Antibody and Pregnancy Complicationsmentioning
confidence: 99%